The Relationship Between Production Cost Budgeting and The Financial Performance Of Seblak Soba Culinary Business In Tasikmalaya - Iin Safariah; Seilla Monica (CV Putra Publisher, 2026)
This study examined the relationship between production cost budgeting and perceived financial performance at Seblak Soba, a culinary micro, small, and medium enterprise in Tasikmalaya. The study used a quantitative associative design with a survey method. The population consisted of 32 owners and employees directly involved in production and operations, all of whom were selected through saturated sampling. Data were collected through questionnaires supported by observation, interviews, and documentation. The questionnaire used a five-point Likert scale and the data were transformed using the Method of Successive Interval. Instrument quality was assessed through Pearson product-moment validity and Cronbach's alpha reliability tests. Data analysis included descriptive statistics, classical assumption tests, simple linear regression, coefficient of determination, and t testing using IBM SPSS. The results showed a positive and statistically significant association between production cost budgeting and perceived financial performance (B = 0.497; beta = 0.532; t = 3.445; p = 0.002). The regression equation was Y = 14.875 + 0.497X, with R2 = 0.283. Because the data were based on perceptions from 32 respondents within one business, the findings should be interpreted as a context-specific association rather than evidence of a causal increase in actual revenue.